The Role of Cloud Computing Adoption and Firm Performance Using SMEs Technological and Environmental Contexts in Hospitality Industry of Henan, China - Hui, Zhang; Mohammadi, Alireza (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose: The present study focuses on the role of cloud computing adoption and its impact on  firm performance in the hospitality industry of Henan, China, with a focus on Small and  Medium-sized Enterprises (SMEs). Moreover, the study analyses this relationship within the  technological and environmental contexts of the region, providing empirical evidence of the  impact of cloud technology adoption on the performance outcomes of SMEs.  Method: The research employs a quantitative research design, using surveys as the tool for  data collection. The population of the study consisted of SME managers in the hospitality sector  of Henan. Thus, the quantitative research methodology helped evaluate the relationships  between the variables of the present study. The statistical analysis of the data gathered through  the survey evaluated the hypothesized relationships.  Findings: The empirical findings of the present study revealed a significant impact of cloud  computing adoption on the environmental, financial, and social performance of SMEs in the  hospitality sector.  Conclusion: The present study offers data-driven insights into the ways to maximize the  benefits of cloud computing in the technological and environmental contexts of SMEs.  However, the findings of the study are limited to the context of the hospitality sector of Henan,  therefore, its findings do not reflect the other industrial sectors in varying regional contexts.
Keywords: Cloud computing; firm performance; technological and environmental contexts; hospitality industry